Randomized Trial of Dilute Betadine Soak and Scrub for Orthopaedic Foot and Ankle Surgery. Issue 4 (22nd October 2020) - Bohl, Daniel D.; Mehraban, Nasima; Rossi, David; Wakefield, Connor; Lin, Johnny L.; Lee, Simon; Hamid, Kamran S.
Category: Lesser Toes; Midfoot/Forefoot; Other Introduction/Purpose: There is no consensus as to which skin antiseptic technique is most effective at reducing bacterial load prior to orthopaedic foot and ankle procedures. The purpose of this study is to determine if the addition of a dilute betadine soak and scrub to a standard preparation with alcohol and chlorhexidine decreases positive bacterial culture rates from the hallux nailfold. Methods: In this prospective, randomized controlled trial, 242 subjects were randomized to one of two groups. The control group received only a standard skin antiseptic preparation with alcohol and chlorhexidine, while the intervention group received a three-minute dilute betadine soak and scrub followed by the standard preparation with alcohol and chlorohexidine (Figure 1). Immediately before skin incision, culture swabs were taken from the hallux nailfold of both groups. Results: Of the 257 subjects enrolled and randomized, 242 (94.2%) completed the study, satisfying the a priori sample size requirement of 242 subjects. There were no crossovers between groups. There were no differences in baseline characteristics between groups (p>0.05 for each). There was no difference in the bacterial growth rate between groups (26.8% growth in the intervention group versus 26.9% growth in the control group, p=0.991). Conclusion: The hallux nailfold is one of the most difficult to sterilize areas prior to orthopaedic foot and ankle surgery. This randomized controlled trail found no benefit to adding a three-minute dilute betadine soak and scrub to a standard skin preparation with alcohol and chlorohexidine.